Immunoglobulins concentration and B cell counts as severity markers in adult community-acquired pneumonia: Cross sectional study. Issue 45 (6th November 2020) - Luchsinger, Vivian; Lizama, Luis; Garmendia, María Luisa; Tempio, Fabián; Ruiz, Mauricio; Pizarro, Rolando; Rossi, Patricio; Huenchur, Lucía; Moreno, Cristian; López, Mercedes; Ampuero, Sandra; Larrañaga, Carmen; et al.
Abstract : Abstract: Community-acquired pneumonia (CAP) is a worldwide cause of morbidity and mortality. Immunoglobulins (Igs) and B cells quantification studies in CAP are few and show discrepancies. Serum IgA acts as a powerful natural anti-inflammatory factor, but its role in the CAP has not yet been defined. The highly sensitive xMAP Luminex technique allows better immunoglobulins quantification. The aim of this study was to analyze the relation between clinical severity and circulating Igs and B cells in adults with CAP. Igs (M, A, G1, G2, G3, and G4) and B cells were quantified in peripheral blood of 190 Chilean patients ≥18 years old hospitalized for CAP and in 21 adults without respiratory disease, using xMAP Luminex and flow cytometry, respectively. Clinical history was recorded and PSI and CURB-65 scores were calculated for evaluation of clinical severity. The total IgM, IgG2 and total IgG levels were lower in CAP than in asymptomatic adults ( P  < .05). No significant differences of Igs levels were found between patients classified as severe and mild by PSI and CURB-65 scores. Fatal cases had higher levels of IgA ( P  < .05). No differences in CD19 + B cells frequency was found between CAP and asymptomatic adults ( P  = .40). In PSI severe cases, CD19 + B cells were significantly lower than in mild cases ( P  = .008). No differences were found in CURB-65 severe and mild groups ( P  = .11). In fatal cases (11/82) group, CD19 + B cells frequency was lower than in 71 survivors ( P  = .2). No differences in memory B lymphocytes were detected between asymptomatic and CAP adults, severe and mild patients, survivors and fatal cases ( P  > .05). Serum IgA levels were significantly higher in fatal CAP cases, raising it as a potential biomarker for severe disease considering its relatively universal availability. In PSI severe patients, B cells showed lower levels and could have a role on its physiopathology. Finding new markers rooted in physiopathology could improve the possibility of scoring severe CAP cases. Luminex technology showed promising quantification serum Igs. Abstract : Supplemental Digital Content is available in the text